Engineered Nickel Oxide Nanoparticle Causes Substantial Physicochemical Perturbation in Plants - Manna, Indrani; Bandyopadhyay, Maumita (Frontiers in Chemistry, 2017)
Concentration of engineered NiO-NP in nature is on the rise, owing to large scale industrial uses and human interventions, which have accreted the scope of exposure especially at the primary trophic levels of the ecosystem. Nickel content in air, drinking water and soil is already above permissible limits in most parts of the developed world. Though nickel oxide is an essential micronutrient in the animal system, it has already been graded as a human carcinogen by WHO, and numerous studies have established the toxic nature of nickel in higher dosage in the animal system. Though studies depicting toxicity and bioaccumulation of nickel in plants is documented, the interaction of nickel oxide nanoparticle with plants is not fully a well-studied, well elucidated topic. What is known is that, exposure to nickel oxide nanoparticle, arouses stress response and leads to cytotoxicity and growth retardation in a handful of plants, a defined work on the intricate physicochemical cellular responses and genotoxic challenges has been so far absent. We have tried to fill in such gaps with this study. We planned the work around pertinent hypotheses like: whether NiO-NP cause cytotoxicity in a model plant system (Allium cepa L.)?If so, does internalization of nickel ion (the potent toxic) take place in the tissue? Does internalized NiO-NP create furore in the antioxidant enzyme system of the plant leading to cytotoxicity? In that case, whether the ENP causes genotoxicity and leads to pycknosis of the cell. The study has been designed to assess the change in biochemical profile and genotoxicity potential of NiO-NP at a wide range of concentrations using root tips of Allium cepa L., the model system for study of cytotoxicity and genotoxicity, and four of its closest relatives, Allium sativum L., Allium schoenoprasum L., Allium porrum L., Allium fistulosum L., chosen for their immense economic importance. Growing root tips were treated with seven different concentrations of NiO-NP suspension (10 mg L‾1, 25 mg L‾1, 50 mg L‾1, 62.5 mg L‾1, 125 mg L‾1, 250 mg L‾1 and 500 mg L‾1) along with deionised distilled water as negative control and 0.4mM EMS solution as